(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the issues of improving the software and methodological support for teaching the subject "Programming" in the process of training future computer science teachers. Also, ways of integrating modern information and communication technologies into the educational process, effective use of interactive methods and electronic educational resources were analyzed.